2006
DOI: 10.1345/aph.1g409
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Supplementing with Coenzyme Q10 During Statin Therapy

Abstract: Routine CoQ10 supplementation for all patients taking statins to prevent myotoxicity is not recommended. However, certain subpopulations might be at risk and warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 31 publications
0
25
0
1
Order By: Relevance
“…Chronic inhibition of HMG-CoA reductase can lead to decreased levels of numerous non-sterol metabolites that are essential for cell viability (Levy and Kohlhaas, 2006). Furthermore, recent clinical studies suggest that the use of high doses of statins may lead to an increased risk of developing type II diabetes.…”
Section: Isoprenoids Fpps/ggpps and Neurodegeneration—the Current Hypmentioning
confidence: 99%
“…Chronic inhibition of HMG-CoA reductase can lead to decreased levels of numerous non-sterol metabolites that are essential for cell viability (Levy and Kohlhaas, 2006). Furthermore, recent clinical studies suggest that the use of high doses of statins may lead to an increased risk of developing type II diabetes.…”
Section: Isoprenoids Fpps/ggpps and Neurodegeneration—the Current Hypmentioning
confidence: 99%
“…However, the results of our studies and other authorities contradict this hypothesis [3,12]. Apart from inhibition of cholesterol (CH) biosynthesis, statins block the synthesis of the major antioxidant compound ubiquinone (ubiphenol) Q 10 [10] protecting plasma low-density lipoproteins (LDL) from atherogenic oxidative modification. Statins also block the synthesis of selenoproteins (e.g., Se-containing glutathione peroxidase utilizing lipid hydroperoxides) [12].…”
mentioning
confidence: 54%
“…The only randomised controlled clinical trials investigating this area showed contrasting results and further well-performed clinical trials are needed to investigate whether CoQ 10 can be used to support statin therapy. Although several studies have shown that plasma CoQ 10 levels are decreased after statin therapy, existing evidence also suggests that skeletal muscle CoQ 10 levels are not affected or even increased after statins (113,115,116) .…”
Section: Effects Of Combination Therapy With Coenzyme Q 10 and Statinsmentioning
confidence: 99%